Advocates of ‘an unpopular cause’: Frances Ames, Helen Suzman and Cannabis Decriminalisation in South Africa (Historia, 2023)
Two South African professional women were early advocates of cannabis decriminalisation during the second half of the twentieth century. Frances Ames (1920-2002) was a neurologist and psychiatrist based at the Medical School of the University of Cape Town. Helen Suzman (1917-2009) represented the Progressive Party for 36 years as an opposition member of parliament. This article documents their individual – later allied – activities and arguments, initially in relation to National Party (apartheid) drug control measures and then into the democratic era of the African National Congress. A social history approach reveals continuities and changes in the cannabis policy rationales of successive governments and the challenges made to these policies.
Keywords: cannabis; dagga; drug policy; medical cannabis; Frances Ames; Helen Suzman; drug decriminalisation